Witness : Art and Civil Rights in the Sixties (NY; Brooklyn Museum; Monacelli Press, 2014)
Pubished with a travelling exhibition of the same name. March-July 2014 @Brooklyn Museum, August-Dec 2014 @Hood Museum of Art, Dartmouth College, Feb-May 2015 @ Blanton Museum of Art. Texts: Kelie Jones, Connie H. Choi, Teresa A. Carbone, Cynthia A. Young, Dalila Scruggs.
English
Keywords: N5300-7418 Visual Arts- History; Political role; USA